Manajemen Kelembagaan Badan Usaha Milik Desa (BUMDes) Di Desa Siwarak Kecamatan Karangreja Kabupaten Purbalingga - Chamid Sutikno; Zaula Rizqi Atika; Shadu Satwika Wijaya; Mujib Mujib (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Increasing village development can be achieved by maximizing the village's economic potential and becoming a forum for village community cooperation to independently and actively develop themselves and their own environment. Village communities are equally entitled to participate in expanding and developing for the sake of creating order and prosperity. The establishment of rural community economic institutions known as Village Owned Enterprises (BUMDes) as one of the mainstay programs in increasing village economic independence is one of the new approaches that is anticipated to be able to become the driving force of development and wheels of the village economy. village economy. An in-depth analysis and description of the Management of Village-Owned Enterprises (Bumdes) in Siwarak Village, Karangreja District, Purbalingga Regency is the goal of this community service project. After analyzing the problem, aspects of BUMDes institutional assistance activities can be determined. Asepk which is the focus of the implementation of this community service focuses on organizational management which sees BUMDes development from the aspects of planning, organizing, directing and controlling in carrying out the functions and responsibilities of managing village-owned enterprises (BUMDes)